(untitled) (Journal of Hama University, 2022)
This study was conducted to find out the effect of adding sheep fat to broiler meat on bacterial count and peroxide number to determine the best percentage of fat added to broiler meat in order to preserve it without spoiling for as long as possible. To achieve this, the experiment was conducted on five groups of broiler meat with different percentages of sheep fat added according to the following: B (Control) broiler meat only, nothing was added to it, B1 (broiler meat + 15% fat), B2 (broiler meat + 20% fat), B3 (broiler meat + 25% fat), B4 (broiler meat + 30% fat). Then the peroxide number was measured and a general bacterial count was performed on days (1-2-3-7) after keeping the study groups at a temperature of +4°C, and on days (1-2) after keeping the study groups at a temperature of +25°C. Results showed that There were no significant differences at (P<0.05) with regard to the peroxide number on days (1-2-3) between study groups with a degree of preservation +4°C, while there were significant differences at (P<0.05) regarding the peroxide number between Study groups on the seventh day and the rest of the experiment days at a temperature of +4°C. The results also showed that there were significant differences at (P<0.05) between the control group and the rest of the study groups with regard to the peroxide number on the second day at a temperature of +25°C. As for the bacterial count, significant differences were found at (P<0.05) between the study groups and the control group, in the degrees of preservation +4°C and +25°C. This study concluded that sheep fat can be added to broiler meat in order to improve its specifications, but Within certain percentages to avoid rancidity, the results of this study also showed that the best percentage of added fat was 15%.